Meta-Analysis: The Effects of Depression and Anxiety on the Quality of Life of People with Disability - Nurhayati, Iffah; Murti, Bhisma; Prasetya, Hanung (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: A person with a disability is a person who has (suffers) a disability/ limitations in the structure and function of the body which can cause problems in their life. Environmental conditions (physical, biological and social) that are not disability-friendly will have an impact on mental problems and the most common are depression and anxiety. Depression and anxiety have an important influence on the health conditions and quality of life of persons with disabilities. The purpose of this study was to analyze the effect of depression on the quality of life of persons with disabilities and to analyze the effect of anxiety on the quality of life of persons with disabilities.Subjects and Method: The meta-analysis was carried out by systematically reviewing the same number of articles from PubMed, Science Direct, and Google Scholar. This is done using the search keywords